Low but measurable stimulated serum thyroglobulin levels <2 µg/L frequently predict incomplete response in differentiated thyroid cancer patients. (November 2014) - Aldawish, Mohammed; Jha, Naresh; McEwan, Alexander J. B.; Severin, Diane; Ghosh, Sunita; Morrish, Donald W.
Abstract Introduction: The study was aimed to determine the response and predictive risk factors of differentiated thyroid cancer (DTC) with measurable (0.4–2.0 µg/L) stimulated serum thyroglobulin (sTg) during the 10–24 months after radioiodine remnant ablation (RRA) and their long-term outcomes. Methods: Out of 839 retrospectively reviewed patients, 95 eligible DTC patients were included. Patients were classified as having incomplete response or no evidence of disease (NED). The sTg cut-off values with highest predicted accuracy for incomplete response at 10–24 months were calculated with receiver operator characteristics curve analysis. Results and Conclusion: At 10–24 months after RRA, incomplete response was identified in 54 patients (57%) and 38/54 (70.4%) patients were found with structural evidence of disease. The remaining 16 patients (29.6%) had biochemical evidence of disease without structural evidence of disease. Forty-one patients (43%) were classified as having NED at 10–24 months after RRA and 27 patients (66%) did not receive further radioactive iodine (RAI) therapy and remained disease free at median follow-up of 6.5 years. Fourteen patients received second RAI treatment after 6 months and before the 10–24 months assessment time point. Of these, 2 had persistent tumor 6 years later. The sTg >0.6 µg/L at 6–10 months after RRA had optimal sensitivity (83.3%), specificity (56%) and negative predictive value (72%) of detecting incomplete response at 10–24 months after RRA. A total of 23/43 patients in the American Thyroid Association low-risk category had incomplete response after first RRA and 5/23 (21.7%) had recurrent/persistent disease at long-term follow-up.